2015
DOI: 10.1016/j.enconman.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic steam reforming of tar derived from steam gasification of sunflower stalk over ethylene glycol assisting prepared Ni/MCM-41

Abstract: Ethylene glycol (EG) assisted impregnation of nickel catalyst on MCM-41 (Ni/MCM-41-EG) was performed and applied for steam reforming of tar derived from biomass. The catalyst was characterized by SEM-EDX, BET, XRD, and TPR. It is found that smaller nickel particles were well dispersed on MCM-41 and better catalytic activity was shown for the Ni/MCM-41-EG when compared with the catalyst of Ni/MCM-41 prepared by using the conventional impregnation method. H 2 yield increased approximately 8 % when using 20 wt.% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 48 publications
(56 reference statements)
1
40
0
1
Order By: Relevance
“…It should be noted that the diffraction peak intensities of Al2O3-0.5 are weak, indicating that the use of CTAB to modify in the Al2O3 porous structure could retard the crystallization to some extent [18]. Interestingly, after metal is doped on Al2O3-0.5, the diffraction intensities increase due to the incorporation between loaded metal with Al2O3 structure [19]. Moreover, one can see that some new phases, i.e., ZnAl2O4, CeAlO3, NiAl2O4 are also observed in spite of no appearance of diffraction peaks attributed to metal species of Zn, Ce and Ni.…”
Section: Characterizations Of Catalystmentioning
confidence: 89%
See 3 more Smart Citations
“…It should be noted that the diffraction peak intensities of Al2O3-0.5 are weak, indicating that the use of CTAB to modify in the Al2O3 porous structure could retard the crystallization to some extent [18]. Interestingly, after metal is doped on Al2O3-0.5, the diffraction intensities increase due to the incorporation between loaded metal with Al2O3 structure [19]. Moreover, one can see that some new phases, i.e., ZnAl2O4, CeAlO3, NiAl2O4 are also observed in spite of no appearance of diffraction peaks attributed to metal species of Zn, Ce and Ni.…”
Section: Characterizations Of Catalystmentioning
confidence: 89%
“…Moreover, one can see that some new phases, i.e., ZnAl2O4, CeAlO3, NiAl2O4 are also observed in spite of no appearance of diffraction peaks attributed to metal species of Zn, Ce and Ni. It indicates that metal species should be well distributed on Al2O3 structure, which could lead to the reduction of sintering, accumulation and deactivation during the thermal reactions [19]. (Fig.…”
Section: Characterizations Of Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, impregnating the 1%Ru‐Ni/MCM‐41 with Mg reduced the reverse water gas shift reaction (RWGSR) and subsequently enhanced catalytic efficiency that resulted in higher CH 4 conversion. Karnjanakom et al investigated the SR of tar derived from biomass using Ni/MCM‐41 assisted with ethylene glycol (EG) . Their research showed that tiny Ni particles were well spread on MCM41 and good catalytic activity was revealed for the Ni/MCM‐41‐EG.…”
Section: Introductionmentioning
confidence: 99%